2021
DOI: 10.7150/thno.50150
|View full text |Cite
|
Sign up to set email alerts
|

Blocking NHE1 stimulates glioma tumor immunity by restoring OXPHOS function of myeloid cells

Abstract: Background: Immunosuppressive tumor microenvironment (TME) in glioblastoma (GBM) is one of the contributing factors for failed immunotherapies. Therefore, there is an urgent need to better understand TME and to identify novel modulators of TME for more effective GBM therapies. We hypothesized that H + extrusion protein Na/H exchanger 1 (NHE1) plays a role in dysregulation of glucose metabolism and immunosuppression of GBM. We investigated the efficacy of blockade of NHE1 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 57 publications
(58 reference statements)
0
32
0
Order By: Relevance
“…Bulk RNA sequencing and bioinformatic analysis were performed in P2RY12 + microglia samples sorted by MACS and paired-end sequenced in the platform of Illumina HiSeq X, as in our recent report 82 . Briefly, the library was prepared using the SMARTer stranded total RNA pico V2 kit (Takara Bio, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk RNA sequencing and bioinformatic analysis were performed in P2RY12 + microglia samples sorted by MACS and paired-end sequenced in the platform of Illumina HiSeq X, as in our recent report 82 . Briefly, the library was prepared using the SMARTer stranded total RNA pico V2 kit (Takara Bio, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial stress tests were performed using Seahorse extracellular flux analyzer (Agilent Technologies) per the manufacturer’s instruction, as we reported recently 82 . P2RY12 + microglial cells were isolated from 3-day poststroke brain tissues using MACS, as described above.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously recognized that GAMs undergo constant epigenetic and metabolic reprogramming regarding oxidative phosphorylation and anaerobic glycolysis, swinging between pro- and anti-inflammatory responses for growth-promoting or tumor-killing activity ( 51 – 54 ). Anti-inflammatory GAMs use the tricarboxylic acid (TCA) cycle in mitochondria to produce electrons that are essential for oxidative phosphorylation of glucose to generate high amounts of adenosine triphosphate (ATP) ( 55 ).…”
Section: Glioma-associated Microglia/macrophages (Gams)mentioning
confidence: 99%
“…focused on the effect of Na/H exchanger 1 in combination with TMZ on immunotherapy. They found that NHE1 was closely related to the immunosuppressive TME of GBM, which is one of the reasons for downregulating the sensitivity of GBM to the immune response ( 150 ). And further validated the effect of combination treatment of NHE1 inhibitor HOE642 with TMZ on PD-1.…”
Section: Combined Dna Damage Repair-based Therapy With Immunotherapymentioning
confidence: 99%